The capability of chloramphenicol biotransformation of Klebsiella sp. YB1 under cadmium stress and its genome analysis. (February 2023) - Tan, Zewen; Yang, Xiuyue; Liu, Yiling; Chen, Lian; Xu, Huijuan; Li, Yongtao; Gong, Beini
Abstract: Co-contamination by antibiotics and heavy metal is common in the environment, however, there is scarce information about antibiotics biodegradation under heavy metals stress. In this study, Klebsiella sp. Strain YB1 was isolated which is capable of biodegrading chloramphenicol (CAP) with a biodegradation efficiency of 22.41% at an initial CAP of 10 mg L −1 within 2 days. CAP biodegradation which fitted well with the first-order kinetics. YB1 still degrades CAP under Cd stress, however 10 mg L −1 Cd inhibited CAP biodegradation by 15.1%. Biotransformation pathways remained the same under Cd stress, but two new products (Cmpd 19 and Cmpd 20) were identified. Five parallel metabolism pathways of CAP were proposed with/without Cd stress, including one novel pathway (pathway 5) that has not been reported before. In pathway 5, the initial reaction was oxidation of CAP by disruption of C –C bond at the side chain of C1 and C2 with the formation of 4-nitrobenzyl alcohol and CY7, then these intermediates were oxidized into p -nitrobenzoic acid and CY1, respectively. CAP acetyltransferase and nitroreductase and 2, 3/4, 5-dioxygenase may play an important role in CAP biodegradation through genome analysis and prediction. This study deepens our understanding of mechanism of antibiotic degradation under heavy metal stress in the environment. Graphical abstract: Image 1 Highlights: Klebsiella sp. YB1 is capable of biodegrading chloramphenicol even under Cd stress. Two novel biotransformation products were identified only with Cd stress. Five parallel biotransformation pathways were proposed, including a novel pathway. CAP-acetyltransferase and 2, 3/4, 5-dioxygenase play a key role in biotransformation. Biodegradation was the main mechanism of chloramphenicol removal of strain YB1.